RELATIONSHIP OF THE INTER-CONDYLAR WIDTH WITH MANDIBULAR INTER-CANINE WIDTH - Qamar, Khezran; Shaikh, Irfan Ahmed; Naeem, Sajid (Journal of Ayub Medical College Abbottabad, 2013)
Background: Aesthetic tooth selection and physiological tooth arrangement are the objectives of the complete denture fabrications. The objective of this study was to determine the relationship of the inter-condylar width with mandibular inter-canine width. Methods: This cross-sectional comparative study was conducted in Department of Prosthodontics, Lahore Medical and Dental College, Lahore from January to June 2011. A total of 250 dentate subjects were selected according to the inclusion criteria. Maxillary and mandibular arch impressions were taken. The distance between the cusp tips of mandibular canines was measured by using vernier calliper. The inter condylar width was measured using arbitrary face bow. The width between the two condylar rods was measured with vernier calliper in millimetres. Every width was measured three times by the same operator to ensure the accuracy. Data recorded on the Performa for statistical analysis. Result: Pearson correlation coefficients (r) for the inter condylar width and mandibular inter-canine are showing positive correlation and significant (r=0.24, p=0.0005). Conclusions: Inter-condylar width provides significant measurements for the selection of anterior teeth in edentulous patients. Keywords: Inter-condylar width, Inter-canine width, Aesthetic, Complete denture, Edentulous, Tooth selection